Personal finance planning the factors of acceptance of Islamic banking / Kahairul Abd Karim Mohamad - Abd Karim Mohamad, Kahairul (Faculty of Business and Management, 2010)
Islamic banks have been operating like other traditional bank about four decades. They also mobilize deposits and produce loans based on Islamic Law (Shari’ah), which are different from the other conventional or commercial banks. Therefore, Islamic banking differs from conventional banking in several ways, such as the prohibition of transactions based on interest rate and the requirement that bank’s operations be carried out according to certain procedures through the use of certain financial instruments [Abdu lQawi, O. and O. Lynn, 2001.]. However, the Islamic bank can also offer products and services which are similar to those offered by a conventional bank. Generally, we can define the Islamic bank as a non-interest based financial institution which complies fully with Islamic Laws and has creative and progressive financial engineering to offer efficient and competitive banking, investment, trade finance, commercial and real estate financing services [Abdul Qawi, O. and O. Lynn, 2001.].